2019
DOI: 10.1007/s00299-019-02494-y
|View full text |Cite
|
Sign up to set email alerts
|

Male and female inheritance patterns in tetraploid ‘Moncada’ mandarin

Abstract: Key message Tetraploid `Moncada´ mandarin, used as male and female in interploidy hybridizations, displays mainly tetrasomic inheritance for most LGs, with slight variations according to the direction of the crossing. Abstract Triploid-breeding programs in citrus are key tool to develop seedless cultivars. Obtaining triploid citrus hybrids may be achieved through different strategies, such as the exploitation of female unreduced gamete in crosses between diploid parents and diploid by tetraploid sexual hybridi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 75 publications
0
7
0
Order By: Relevance
“…The inheritance patterns of molecular markers are powerful tools for determining meiotic behavior in polyploid species. They have been successfully used in citrus for doubled diploids [47,57,58,87] and somatic hybrids [46,73,88]. Indeed, the genetic structure of diploid gamete populations produced by tetraploid parents and particularly parental heterozygosity restitution depends on preferential chromosome pairing and on the double reduction rate with two extreme models, disomic and tetrasomic [42,44,89].…”
Section: The Two Tetraploid Intergeneric Hybrids Display Intermediatementioning
confidence: 99%
See 1 more Smart Citation
“…The inheritance patterns of molecular markers are powerful tools for determining meiotic behavior in polyploid species. They have been successfully used in citrus for doubled diploids [47,57,58,87] and somatic hybrids [46,73,88]. Indeed, the genetic structure of diploid gamete populations produced by tetraploid parents and particularly parental heterozygosity restitution depends on preferential chromosome pairing and on the double reduction rate with two extreme models, disomic and tetrasomic [42,44,89].…”
Section: The Two Tetraploid Intergeneric Hybrids Display Intermediatementioning
confidence: 99%
“…maxima gene pool revealed preferential tetrasomic inheritance. This was the case of doubled diploids of clementine [57] and 'Moncada' mandarin [87] as well as for a somatic hybrid between 'Nova' tangelo and 'HB' pummelo [88]. Rouiss et al [47] suggested that the PP rate, and more generally meiotic behavior, is determined by the phylogenomic structure of the tetraploid parents.…”
Section: The Two Tetraploid Intergeneric Hybrids Display Intermediatementioning
confidence: 99%
“…In the framework of our triploid breeding program, we obtained a large number of doubled diploid plants from non-apomictic genotypes using antimitotic chemicals, and it is important to point out differences in pollen performance and viability between them. For example, stable doubled diploid plants of “Chandler” pummelo and “Moncada” ( Garavello et al, 2020 ), “Temple,” and “Encore” mandarins have good pollen performance, whereas other doubled diploid mandarin varieties like “Wilking,” “Marisol,” and “Fina” clementines display less pollen performance. In other crop species like flax, sunflower, barley, and cotton ( Luckett, 1989 ; Yemets and Blume, 2008 ; Ahmadi and Ebrahimzadeh, 2020 ), it has been observed that colchicine can cause chromosome loss or rearrangement and gene mutations, which could affect the viability of pollen grains.…”
Section: Discussionmentioning
confidence: 99%
“…There are several methods for estimating polyploid allele dose, among which KASPar technology [ 39 , 43 ] and QF-PCR [ 44 , 45 ] are widely applicable. KASPar technology is similar to TaqMan technology, and this method requires a high-density SNP database and genome-wide association analysis [ 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…In the preferential pairing of homologous chromosomes, the transmission of parental heterozygosity decreases as the tetrasomy rate (τ) increases [ 80 ]. Garavello et al [ 45 ] found that the Parental heterozygosity restitution (PHR) of tetraploid ‘Moncada’ female gametes was higher and that the progenies of tetraploid female parents presented higher genotype consistency with the parent. Accurate assessment of preferential pairing and multivalent formation in tetraploids can accelerate the accumulation of rare but advantageous alleles through MAS [ 46 , 48 ].…”
Section: Discussionmentioning
confidence: 99%